Formation of professional competence in students - Maʼmurova , Feruza; Nuriddinov , Akmal; Abdullaeva , Mukhlisa (The Lingua Spectrum, 2025)
Nowadays, every specialist is required to continuously enrich their knowledge, study new information, understand the demands of the present time, develop the ability to seek new knowledge, process it, and apply it in their practical activities. In this article, the author highlights one of the most pressing issues of today - the formation of professional competence in students. Additionally, the article explores the concept of competence and it types, which have been extensively studied by scholars from foreign countries.